2007
DOI: 10.4315/0362-028x-70.11.2626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Essential Oils of Oregano and Nutmeg on Growth and Survival of Yersinia enterocolitica and Listeria monocytogenes in Barbecued Chicken

Abstract: The in vitro effects of plant essential oils (EOs) against pathogenic bacteria are well known, yet few studies have addressed the effects of these compounds against pathogens associated with ready-to-cook foods. Experiments were conducted to determine the effectiveness of oregano and nutmeg EOs on the growth and survival of Yersinia enterocolitica and Listeria monocytogenes in broth culture and in Iranian barbecued chicken. Ready-to-cook Iranian barbecued chicken was prepared according to the common practice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 38 publications
3
26
0
1
Order By: Relevance
“…Oregano, one kind of labiate Origanum plant that has been popular for a long time in folk medicine, is a very versatile plant. The antibacterial activity of the essential oils of oregano and thyme have been documented against Escherichia coli O157:H7 and Listeria monocytogenes (Aboaba et al, 2006;Dimitrijevic et al, 2007;Firouzi et al, 2007;Govaris et al, 2011;de Medeiros Barbosa et al, 2016). In the work by Medeiros Barbosa et al (2016) the antibacterial eff ects of oregano and rosemary essential oils against Escherichia coli, Listeria monocytogenes and Salmonella were presented.…”
Section: Plant Extracts In Chemoprevention Andmentioning
confidence: 99%
“…Oregano, one kind of labiate Origanum plant that has been popular for a long time in folk medicine, is a very versatile plant. The antibacterial activity of the essential oils of oregano and thyme have been documented against Escherichia coli O157:H7 and Listeria monocytogenes (Aboaba et al, 2006;Dimitrijevic et al, 2007;Firouzi et al, 2007;Govaris et al, 2011;de Medeiros Barbosa et al, 2016). In the work by Medeiros Barbosa et al (2016) the antibacterial eff ects of oregano and rosemary essential oils against Escherichia coli, Listeria monocytogenes and Salmonella were presented.…”
Section: Plant Extracts In Chemoprevention Andmentioning
confidence: 99%
“…This study opened the possibility of using these natural compounds in the food industry after slaughter to inhibit salmonella. Firouzi et al [13] tested the EO from oregano and nutmeg on the survival of Y. enterocolitica and l. monocytogenes in a broth system and on barbecued chicken. In the broth system, they found that the nutmeg EO exhibited a greater effect on l. monocytogenes than the oregano EO and that the oregano EO had a greater effect on Y. enterocolitica than the nutmeg EO.…”
Section: Essential Oilsmentioning
confidence: 99%
“…aureus (Anonymous, 1995). Essential oil of nutmeg caused a significant inhibition of growth and survival of Yersinia enterocolitica and Listeria monocytogenes in broth culture and in Iranian barbecued chicken (Firouzi et al, 2007). Takikawa et al (2002) have reported the antimicrobial activity of nutmeg (seeds of M. fragrans) extract against Escherichia coli O157.…”
Section: Antimicrobial Activitymentioning
confidence: 99%